Cloud Computing and Services Science - Ivanov, Ivan.; van Sinderen, Marten; Shishkov, Boris; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
N/A
Object-oriented Service Clouds for Transdisciplinary Computing -- From Service Innovation to Service Engineering -- Adaptive Overlay Approach on the Inter-Cloud Environment -- Securing Virtual and Cloud Environments -- Achieving Market Liquidity through Autonomic Cloud Market Management -- Cost-performance Driven Resource Configuration for Database Applications in IaaS Cloud Environments -- Accelerating Service-oriented Workflows -- An Integrated Monitoring Infrastructure for Cloud Environments -- Service Development Abstraction: A Design Methodology and Development Toolset for Abstractive and Flexible Service-based Sofware -- Cloud Computing Costs and Benefits: An IT Management Point of View -- A Cloud Computing Medical Image Analysis and Collaboration Platform -- Applicability of NoSQL Databases to Mobile Networks: Case Home Location Register -- SLA-based Planning for Multi-domain Infrastructure as a Service -- Scheduling On-demand SaaS Services on a Shared Virtual Cluster -- Assessing Cloud Infrastructure Costs in Communications-intensive Applications -- Exploring Cloud Computing Techniques for Real-time Geoprocessing -- A Performance Evaluation of Block I/O Paravirtualization & Virtual Machine Images -- Dynamic Resource Allocation for Multi-tiered, Cluster-based Web Hosting Environments -- A Method for Experimental Analysis and Modeling of Virtualization Performance Overhead -- The Partition Cost Model for Load Balancing in MapReduce -- Author Index.
Keywords: Computer science; Information Systems; Engineering economy; Economics; Business planning; Computer Science; Management of Computing and Information Systems; Operations Research/Decision Theory; Organization/Planning.; Business/Management Science, general; Engineering Economics, Organization, Logistics, Marketing